Early diagenesis : a theoretical approach - Berner, Robert A., 1935- (Princeton series in geochemistry., 1980)
The approach to diagenesis in this book is unorthodox in that it is entirely on the third level. This means that diagenesis is described quantitatively in terms of mathematical rate expression. Our goals will be to develop theoretical models, based on a combination of sediment observations and a priori reasoning, which describe and interrelate in a quantitative manner the various diagenetic processes that affect a given sediment property during early diagensis. Although many important diagenetic problems will be addressed, it is not our purpose to discuss each mineral type, sediment type, etc., in terms of natural observations and thermodynamic equilibrium (levels one and two). The topics covered in the last three chapters are chosen merely to illustrate the power of the mathematical models developed in the previous three chapters and not to provide a survey either of diagenetic processes or of the products of these processes. Thus, the scope of the book is narrow but very deep. This is done partly out of necessity because much of the rate data upon which diagenetic models must rest has not yet been obtained